The origin and the genetic regulation of the self-compatibility mechanism in clementine (Citrus clementina Hort. ex Tan.) - Bennici, Stefania; Poles, Lara; Di Guardo, Mario; Percival-Alwyn, Lawrence; Caccamo, Mario; Licciardello, Concetta; Gentile, Alessandra; Distefano, Gaetano; La Malfa, Stefano (Frontiers in Plant Science, 2024)
Self-incompatibility (SI) is a genetic mechanism common in flowering plants to prevent selffertilization. Among citrus species, several pummelo, mandarin, and mandarin-like accessions show SI behavior. In these species, SI is coupled with a variable degree of parthenocarpy ensuring the production of seedless fruits, a trait that is highly appreciated by consumers. In Citrus, recent evidences have shown the presence of a gametophytic SI system based on S-ribonucleases (S-RNases) ability to impair self-pollen tube growth in the upper/middle part of the style. In the present study, we combined PCR analysis and next-generation sequencing technologies, to define the presence of S7-and S11-Rnases in the S-genotype of the Citrus clementina (Hort. ex Tan.), the self-incompatible 'Comune' clementine and its self-compatible natural mutant 'Monreal'. The reference genome of 'Monreal' clementine is presented for the first time, providing more robust results on the genetic sequence of the newly discovered S7-RNase. SNP discovery analysis coupled with the annotation of the variants detected enabled the identification of 7,781 SNPs effecting 5,661 genes in 'Monreal' compared to the reference genome of C. clementina. Transcriptome analysis of unpollinated pistils at the mature stage from both clementine genotypes revealed the lack of expression of S7-RNase in 'Monreal' suggesting its involvement in the loss of the SI response. RNA-seq analysis followed by gene ontology studies enabled the identification of 2,680 differentially expressed genes (DEGs), a significant number of those is involved in oxidoreductase and transmembrane transport activity. Merging of DNA sequencing and RNA data led to the identification of 164 DEGs characterized by the presence of at least one SNP predicted to induce mutations with a high effect on their amino acid sequence. Among them, four candidate genes referring to two Agamous-like MADS-box proteins, to MYB111 and to MLO-like protein 12 were validated. Moreover, the transcription factor MYB111 appeared to contain a binding site for the 2.0-kb upstream sequences of the S7-and S11-RNase genes. These results provide useful information about the genetic bases of SI indicating that SNPs present in their sequence could be responsible for the differential expression and the regulation of S7-RNase and consequently of the SI mechanism.